Pengaruh Literasi Keuangan dan Pengendalian Diri terhadap Perilaku Konsumtif Mahasiswa - Diary Prihatini; Agus Irianto (Universitas Negeri Padang, 2021)
This study aims to determine and analyze 1) the effect of financial literacy on the consumptive behavior of students of the Economics Faculty of Padang State University 2) the effect of self-control on the consumptive behavior of students of the Economics Faculty of Padang State University, and 3) the effect of financial literacy on self-control. This type of research is an inferential descriptive study. The sampling technique used in this study was proportional random sampling technique with a sample of 86 students. The data analysis technique used in this research is descriptive analysis and path analysis. The results showed that (1) financial literacy has a significant effect on the consumptive behavior of students of the Economics Faculty of Padang State University, (2) Self-control has a significant effect on the consumptive behavior of students in the Economics Faculty of Padang State University, and (3) Financial literacy has a significant effect on self-control of students in the Economics Faculty of State University field.Abstrak ditulis salam bahasa inggris, menggunakan jenis huruf Palatino Linotype 10 pt spasi satu, Max 200 kata.Keywords : financial literacy, self-control, consumptive behavior